Self-assembled one dimensional functionalized metal–organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical communications (Cambridge, England), 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In- and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 × 10(-5) and 3.61 × 10(-3) S cm(-1) respectively.